Conceptual Models for the Implementation of Mobile Technologies in Cultural Heritage Organizations - Pacetti-Donelson, Vandy (Qualitative and Quantitative Methods in Libraries; Vol 9 No 3 (2020): September Issue 2020, 2020)
Mobile devices have an important role in society in that they have already supplanted other means of information seeking tools as the primary preference for users to find the latest news, entertainment, and educational information. Increasingly, cultural heritage organizations have implemented mobile technologies to provide visitors with an empowered cultural experience. Choosing an adequate formal process for mobile application design and implementation has become an important success requirement. However, there is little, if any, review research analyzing and synthesizing existing models and frameworks for designing mobile cultural heritage environments. This work presents a systematic review, which will categorize and synthesize information from several studies that provide design frameworks or conceptual models in order to implement mobile experiences into the presentations from cultural heritage organizations. This review will provide insights and may inform practitioners as well as mobile application designers and researchers who are interested in providing meaningful mobile learning experiences and environments based on sound theoretical foundations.